Fabrication of SERS Substrates Using Ag/SiO₂ Nanocomposite for Dectecting Sub-ppm Glucose Concentration - Van Hong, Bui; Giang, Nguyen Thi Huong (VNU Journal of Science: Mathematics - Physics, 2026)
This work presents the fabrication of an Ag/SiO₂ nanocomposite (NC) using the Stöber method coupled with chemical reduction, which serves as an effective SERS platform for the ultrasensitive detection of glucose at sub-ppm concentrations. SEM analysis revealed that the SiO₂ is in the form of nanospheres (NSs) with an average diameter of 159 nm, while TEM images showed Ag nanoparticles (NPs) with an average diameter of approximately 17 nm, uniformly distributed on the SiO₂ surface. Such a well-defined nanostructure optimizes the SERS performance by providing distinct Raman signals corresponding to the functional groups in glucose molecules. In this study, glucose was successfully detected in the concentration range from 20 ppm down to 1 ppm, with a characteristic Raman peak observed at 1334 cm⁻¹.